Tambourine Art as a Da'wah Strategy in the Actualization of Islamic Values in Islamic Religious Education Learning - Rahmatiah Rahmatiah; Asna Isa (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of this research is to determine the art of tambourine as a da'wah strategy in the actualization of Islamic values in Islamic religious education learning. Methodology: This research uses a qualitative approach with a case study method. The instrument used in data collection was an interview sheet. This research data analysis will use a qualitative data analysis approach by Miles and Huberman which includes data collection, data reduction, data presentation, and drawing conclusions. Main Findings: The results of this research are the integration of local wisdom values, especially through Tambourine Art, in Islamic Religious Education learning which has a positive impact in strengthening students' understanding of local religious and cultural values. Learning that is contextual and relevant to students' lives can make a significant contribution to the formation of strong character rooted in noble religious values. Novelty/Originality of this study: The use of Tambourine Art as a Da'wah Strategy in Islamic Religious Education learning provides a holistic learning approach, combining aspects of art, culture and religion in one container. This can enrich students' learning experience and help them to better understand Islamic teachings as a whole.